2010
DOI: 10.1557/proc-1269-ff02-05
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Morphology, Water Uptake, and Proton Conductivity in Radiation Grafted Proton Exchange Membranes

Abstract: A small-angle neutron scattering (SANS) investigation of saturated aqueous proton exchange membranes is presented. Our membranes were synthesized by radiation-induced grafting of poly(ethylene-alt-tetrafluoroethylene) (ETFE) with styrene in the presence of crosslinker (divinylbenzene, DVB) and the polystyrene was sulfonated subsequently. The contrast variation method was used to understand the relationship between morphology, water uptake, and proton conductivity. We find that the membranes are separated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This result suggests that the PS-graft regions existed at regular spatial intervals of 30 nm. In previous SANS measurements of the FEP-and ETFE-based PS-grafted films, 7,9 this peak was also observed at a similar q. However, the interpretation of this peak was not so clear in these studies.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…This result suggests that the PS-graft regions existed at regular spatial intervals of 30 nm. In previous SANS measurements of the FEP-and ETFE-based PS-grafted films, 7,9 this peak was also observed at a similar q. However, the interpretation of this peak was not so clear in these studies.…”
Section: Resultsmentioning
confidence: 67%
“…However, the interpretation of this peak was not so clear in these studies. 7,9 Thus, the ordered structures responsible for the observed peak in the PS-grafted film were considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, it is worth noting the multiscale nature of proton conduction in PEMs, since the tortuosity and size of ionic channels within each hydrated site affects in turn the value of through the (local effective) proton diffusivity, . As shown in previous works, the membrane processing conditions significantly affect the multiscale morphology of block copolymer membranes [ 75 , 76 , 77 , 78 , 79 , 80 ]. For instance, Assumma et al [ 75 ] reported a ten-fold increase in proton conductivity after thermal annealing of SPAS multiblock copolymer membranes.…”
Section: Resultsmentioning
confidence: 91%